Development of Rapid Viability Test Using Urine Sugar Analysis Paper for Peanut (Arachis hypogaea L.) Seeds - Mubarak, Farahdina; Suhartanto, Mohamad Rahmad; Widajati, Eny (Journal of Tropical Crop Science, 2025)
Seed testing is important for determining seed quality. Seed testing must be easy, quick, and accurate. This study aimed to develop a rapid method for assessing peanut seed quality using Urine Sugar Analysis Paper (USAP). USAP is commonly used for detecting human urinary glucose and is currently being developed for evaluating seed quality. Three experiments were conducted. Experiment 1 investigated the most effective seed-cutting size (whole, halved, and seeds cut into six pieces) and soaking periods (0, 3, 6, and 9 hours) based on glucose and protein leakage, as well as specific gravity of the soaking water. The optimal method identified in Experiment 1 was then used to test all five seed lots in USAP Experiment 2, which aimed to evaluate the effectiveness of seed quality testing using the USAP method at various levels of seed viability. Experiment 3 investigated the correlation between USAP test results and other viability and vigor test parameters, including germination percentage, first count germination, speed of germination, and electrical conductivity. The results of experiments indicated that cutting seeds into six pieces and 6 6-hour soaking period was the most optimal. Experiment 3 showed that USAP testing correlated with viability and vigor testing across various peanut varieties. Protein and density testing using USAP were negatively correlated with germination percentage, first count germination, and germination speed parameters, but positively correlated with electrical conductivity. However, glucose leakage was not detectable using USAP.